STUDI LITERATUR POLA MAKAN DAN KEJADIAN SINDROM DISPEPSIA PADA REMAJA (Jurnal Kesehatan Siliwangi, 2022)
Based on data from Indonesia's health profile in 2011, dyspepsia ranks 5th out of the top 10 inpatient diseases in hospitals and 6th out of 10 outpatient diseases in 2010. Diet includes the type, frequency, and amount of food that is not appropriate. can affect the work of the stomach as one of the factors that greatly influence the occurrence of dyspepsia syndrome in adolescents. The purpose of this study was to determine the description of eating patterns with the incidence of dyspepsia syndrome in late adolescence. The research design used is Systematic Literature Review. The sample used is 7 research journals. There were five studies with the results that there was a relationship between dyspepsia syndrome and diet (p= 0.000; p= 0.001; p= 0.006; p= 0.001; p= 0.003). Meanwhile, two studies showed that there was no relationship between diet and the incidence of dyspepsia syndrome, although the incidence of dyspepsia syndrome was greater in respondents with poor eating patterns (p = 0.987; p = 0.35). It is hoped that further research will use inclusion criteria that are more in line with the results of the study.